The Role of Mothers in Building the Great Historical Islamic Personalities - Khushi Muhammad, Tahira Jabeen; Hassan, Syeda Muneeba; Al-Azhari, Abdul Wahab Jan (Journal of Islamic and Religious Studies, 2023)
Islamic history has immortalized immortal mothers who were symbols of Islam. Their concern was the support of Islam, and the biography presented shining examples of mothers who were generous sources and whose children were the fruits of their cultivation. They were mothers who knew the status of motherhood, the role of the mother in sacrifice and Jihad, and the importance of working on the formation of the Muslim home and raising children armed with the light of knowledge working on the advancement of their religion. Where are the pioneers of the renaissance of motherhood among these models today…? Was the status of the mother - which many people neglected due to the weakness of religious faith - to be restricted to celebrating her one day a year? In this article, we will learn about some shining models from mothers of scholars and venerable preachers who greatly served Islam and spread beneficial knowledge…Perhaps these models will be a shining beacon for mothers today so that these models will guide today‘s mothers in how to raise their children in the light of important Islamic values and meanings.